Forest fires impact on microclimatic and soil conditions in the forests of cryolithic zone (Yakutia, North-Eastern Russia) - L. P. Gabysheva; A. P. Isaev (Сибирский лесной журнал, 2015)
Data analysis on the fire occurrence and frequency in Central Yakutia (North-Eastern Russia) has been considered. Calculate the impact of socio-economic and climatic conditions of region on inflammability parameters. A close relationship was found between quantity and density of population and the frequency of fires occurence (0.95–0.99). Not so much negative correlation observed between the amount of precipitation during the fire-dangerous period and the frequency of fire (–0.53). The results of our study relating to the fire impact on microclimatic and soil conditions of the forests of Central Yakutia are brought in the article. Studies have revealed that strong changes microclimate and soil conditions in the burnt areas occur in the first 10 years after the fire. At the young burned out site, soil temperature in average increases in comparison with the forest at a depth of 5 cm in 5.2 . 5.6 °C, at a depth of 30 cm – in 4.3 . 6.2 °C, soil moisture – by 1.1–2.3 times in a 1–2-year – fire site, by 1.1–1.7 times in a 10–12-year-old one; seasonally thawed layer thickness is 0.3–0.8 m greater in the burned out areas than in the forest. There is stabilization of the modified conditions in the post-fire period in the course of succession. Essential changes of microclimatic and soil conditions occurring after fires and stabilizing in the progress of succession when fire-sites overgrow with plants have been found. In the burned areas of the Central Yakutia it starts at the age of 20–25 years after the fire.